(untitled) (Research Journal on Multi-disciplinary Issues, 2021)
This small piece of writing is an observation-based text highlighting the fact that minority language speakers are indirectly compelled to switch on to the dominant language. This study exclusively highlights how a dialect of Maithili called THETH is losing its ground, and the meaning of some common words is degrading, hence replaced by borrowed terms from the dominant dialect or language of the society. It has attempted to illuminate the fact that upward mobility is reflected in the use of language in everyday life. When the marginalized mass step onto a ladder of success or on the way of upward mobility, they fabricate their personality with different components, of which one is language i.e. dominant language in a general case. This piece of the text aims at exploring the reasons behind opting for the dominant/ influencing language to maintain personality. This is often the case that dominated language betrays the personality of the speakers. So this paper has made a case study at a micro-level along with indirect observation of the related phenomenon. And further, some cases of language use-related events have been analyzed minutely.